(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2018)
In 2012 M. Canevaro and E. M. Harris published an essay about the documents inserted into the text of Andocides’ speech On the Mysteries. These included the decree of Pa- trocleides (Andoc. 1.74-76), the decree of Teisamenus (Andoc. 1.83-84), the so-called New Laws (Andoc. 1.85 and 87) and the Decree of Demophantus (Andoc. 1.96-98). This analysis showed that these documents were forgeries composed during a later period and inserted into the text of On the Mysteries. M. H. Hansen has now attempted to defend the authenticity of the documents found at Andoc. 1.74-76 and 83-84. In this essay, Canevaro and Harris show that his arguments are not convincing and provide additional evidence against the authenticity of these documents.